(untitled) (Environment & Health, 2016)
Objective. We clarified possible mechanisms of the formaldehyde effect on the formation of the population thyroid cancer morbidity. Materials and methods. We analyzed our own data and literary ones with the help of the method of theoretical analysis (generalization, synthesis and abstraction) of the scientific and methodological literature on the biological effects of this compound and the regularities of their manifestation. Results. Formaldehyde inhalation can induce genotoxic and toxic damages in the tissues distant from the primary contact in humans and laboratory animals (circulating blood cells, bone marrow respectively). Furthermore, formaldehyde promotes a carcinogenesis and enhances an immunosupression at the joint administration with other carcinogens. According to these data an induction of genotoxic and toxic changes in thyroid gland and their accumulation at the chronic exposure of formaldehyde with other atmospheric carcinogens may be observed and in conjunction with the immunosupression it may lead to the strengthening of the combined effect and will increase the risk of thyroid cancer among population. Under conditions of the occupational exposure formaldehyde can become a dominant factor in the formation of the professional thyroid cancer morbidity.